Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 2095569 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "TaxonKey is Fungi", "TaxonKey is Stereum hirsutum (Willd.) Pers." ] }, "Country is United Kingdom of Great Britain and Northern Ireland" ] } The dataset includes 2095569 records from 205 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0014745-151016162008034/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences